2002
DOI: 10.1051/radiopro/2002189
|View full text |Cite
|
Sign up to set email alerts
|

Temelín nuclear power plant, South Bohemia - Reference level of hydrosphere, prediction of impact, results from pre-operation period

Abstract: Abstract. Beginning of the construction of Temelin Nuclear Power Plant (NPP) in south Bohemia (CR) dates back to 1986. It was planned that the first water-cooled reactor could be put into operation in 2001. A research project (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998), funded from the national budget and carried out under supervision of the Czech Ministry of Environment, was aimed at examining pre-operational environmental conditions (a reference level) in terms of concentrations of radioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…Higher values seem to refer to short-term studies after Chernobyl accident, where slow wash-off could not clearly be distinguished from rapid wash-off (Foulquier and Baudin-Jaulent, 1990) or where slow wash-off was not fully effective (Saxén, 1994). Lower values seem to correspond to longer term studies, or longer delays after major radionuclide deposits, where much slower trends could be captured (Hanslik et al, 2002(Hanslik et al, , 2005.…”
Section: Slow Wash-offmentioning
confidence: 86%
See 1 more Smart Citation
“…Higher values seem to refer to short-term studies after Chernobyl accident, where slow wash-off could not clearly be distinguished from rapid wash-off (Foulquier and Baudin-Jaulent, 1990) or where slow wash-off was not fully effective (Saxén, 1994). Lower values seem to correspond to longer term studies, or longer delays after major radionuclide deposits, where much slower trends could be captured (Hanslik et al, 2002(Hanslik et al, , 2005.…”
Section: Slow Wash-offmentioning
confidence: 86%
“…In such situations, observed wash-off rate constants reach up to 2%/yr, and are approximately five times higher than for similar watersheds with clay soils. Bergström et al (1997), IAEA (2000), Monte (1993Monte ( , 1995Monte ( , 1997Monte ( , 2001, Smith et al (2004) and Vray et al (2003Vray et al ( , 2005) Liquid wash-off l 1 90 Sr 0.02e0.16 /yr 16 Bergström et al (1997), Monte (1995Monte ( , 2001 and Smith et al (2004) Solid wash-off l 1 137 Cs 0.15e1.56 /yr 10 Maringer (1996), Maringer et al (1997), Monte (1997) and Mundschenk (1996) Total wash-off l 1 137 Cs 0.02e1.53 /yr 42 Aarkrog et al (1991Aarkrog et al ( , 1992, Foulquier and Baudin-Jaulent (1990), Hanslik et al (2005Hanslik et al ( , 2002, Monte (1993Monte ( , 1996, Saxén (1994) and Smith et al (2000) Total wash-off l 1 90 Sr 0.05e0.17 /yr 6 Aarkrog et al (1991Aarkrog et al ( , 1992 Saxén (1994) and Smith et al (2000) Watershed area. Wash-off fluxes are generally higher when monitored on small surfaces.…”
Section: Single Rate Constant (Eqs (5)e(7))mentioning
confidence: 96%
“…Analysis revealed that decreasing trends concentrations of the artificially produced radionuclides could be described by a first order kinetic equation for the whole period of the observation (Hanslı´k et al, 2002;Jedina´kova´-K rı´ zova´and Hanslı´k, 2003). The shape of the kinetic equation for 137 Cs is as follows:…”
Section: Surface Watermentioning
confidence: 97%
“…These samples were dried and ignited. Sampling sites and radiological method were described in proceedings [1].…”
Section: Methodsmentioning
confidence: 99%